(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The content, some problems and prospects of international scientific and technical cooperation within the SCO on the example of the people’s Republic of China and the Republic of Kyrgyzstan are Considered. On the basis of the comparative method, special attention is paid to various sources of legal regulation of scientific and technical activities in these countries.